Perceptions of Secondary School Teachers on the Utilization of Educational Technology - Garnada, Vicpher D. (JPAIR Multidisciplinary Research, 2011)
The study investigated the perceptions of public and private secondary school teachers in selected municipalities of Zamboanga del Sur Province, Mindanao, Philippines on the utilization of educational technology. The descriptive research design is used in which questionnaire was employed as main instrument in gathering data from the 132 public and 34 private secondary school teachers. The study revealed that majority of the respondents was female and more or less 31 years of age. Most of them were taking masters; Makabayan had a great share as to their area of concentration. Nearly everyone was neophytes with permanent status in the service and attended 1 to 3 times on trainings/seminars in educational technology. The public secondary teachers mostly utilized television, DVD player and radio/cassette tape player, while majority of the private secondary teachers utilized computer with internet connection, computer printer and DVD player. The teachers both in public and private secondary schools perceived that they rarely used educational technology in their teaching. They have uncertain disposition towards the role of educational technology. The perceptions of the two groups of respondents were no significant difference between the responses of the public and private secondary school teachers on the utilization of educational technology.